Lontar Yusup Banyuwangi: Warna Lokal dan Variasi Teks dalam Manuskrip Pegon di Ujung Timur Jawa - Indiarti, Wiwin; Hasibin, Nur (Manuskripta, 2019)
Lontar Yusup Banyuwangi (LYB), copied in a Pegon script and still actively read in Banyuwangi, contains the life-story of the Prophet Yoseph from the age of twelve, when he dreamed of the sun, moon and eleven stars bowing to him, until he ascended the throne in Egypt, after his prophecy about King Pharaoh’s dream. The oldest manuscript of LYB, which is found in Kemiren - Banyuwangi and becomes Adi Purwadi’s collection, dates to 1829 in Javanese calendar, presumably derived from an Islamic source, and absorbs various local elements in its textual content. LYB, read with tunes that are intrinsically connected with stanzaic metrical patterns, consists of twelve pupuh (cantos) and four pupuh forms (Kasmaran, Durma, Pangkur, and Sinom) with a total of nearly 600 stanzas. This paper unveils local elements and text variations in LYB which include types of vocabulary usage, forms of tembang variations, and the modification of Perso-Arabic text that makes it different from commons. This shows the high power of local creativity in the writing and copying of manuscripts in the past. === Lontar Yusup Banyuwangi (LYB), disalin dalam aksara pegon dan masih aktif didendangkan di Banyuwangi, menghantarkan kisah Nabi Yusuf dari usia dua belas tahun, saat ia memimpikan matahari, bulan dan sebelas bintang yang bersujud kepadanya, sampai ia naik takhta di Mesir, seusai nubuatnya tentang mimpi Raja Firaun. Naskah tertua LYB berangka tahun Jawa 1829, (koleksi Adi Purwadi dari desa Kemiren, Banyuwangi) diduga berasal dari sumber Islam, dan menyerap berbagai unsur lokal dalam kandungan tekstualnya. LYB berwujud tembang, didendangkan dengan melodi yang secara intrinsik terkait dengan bentuk-bentuk pupuh (serangkaian bait dalam satu episode cerita) - terdiri dari dua belas pupuh, berisi empat bentuk pupuh (Kasmaran, Durma, Pangkur, dan Sinom) dengan total hampir 600 bait. Tulisan ini memaparkan warna lokal dan variasi teks dalam LYB yang meliputi ragam kosakata, bentuk variasi tembang, dan modifikasi teks pegon yang berbeda bentuk penulisannya dengan teks pegon pada umumnya. Hal ini menunjukkan elan kreatifitas lokal yang tinggi dalam penulisan dan penyalinan naskah di masa lalu.